2019
DOI: 10.1161/strokeaha.118.024249
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in 90-Day Poststroke Medication Adherence

Abstract: Background and Purpose— We assessed ethnic differences in medication adherence 3 months poststroke in a population-based study as an initial step in investigating the increased stroke recurrence risk in Mexican Americans compared with non-Hispanic whites. Methods— Ischemic stroke cases from 2008 to 2015 from the Brain Attack Surveillance in Corpus Christi project in Texas were followed prospectively for 3 months poststroke to assess medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Regarding the choice to study statins in the present study, and not, e.g., antihypertensives or anticoagulants also used in ischemic stroke prevention, were based on previous studies showing no significant differences in adherence or persistence to treatment between statins, anticoagulants, and antihypertensives [ 30 , 31 ]. Further, because the SPDR does not contain data of daily doses, the estimates of adherence from SPDR were possible to perform more precisely in statins that merely are prescribed once per day.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the choice to study statins in the present study, and not, e.g., antihypertensives or anticoagulants also used in ischemic stroke prevention, were based on previous studies showing no significant differences in adherence or persistence to treatment between statins, anticoagulants, and antihypertensives [ 30 , 31 ]. Further, because the SPDR does not contain data of daily doses, the estimates of adherence from SPDR were possible to perform more precisely in statins that merely are prescribed once per day.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of recurrent stroke can be reduced if these medications are used appropriately. 5 It is important to evaluate medication adherence (MA) and barriers to MA in secondary stroke prevention. Therefore, it is necessary to investigate the factors causing medication nonadherence in case of recurrent stroke.…”
mentioning
confidence: 99%
“…The patients who did not start or were not prescribed OAC after stroke occurrence (n = 151) were significantly older (82:5 ± 9:1 years; p < 0:001) and had more severe stroke (median NIHSS [IQR] at discharge 12 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; p < 0:001), 82% died within 1 year following the index stroke. The characteristics of patients who were not prescribed OAC and those who did not purchase the prescription were not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…While there have been numerous studies reporting realworld data on OAC use and therapy adherence in AF patients, much less is known about OAC treatment following an ischemic stroke [6][7][8][9][10][11][12][13][14]. These studies on OAC in stroke patients have reported somewhat different results depending on the aim of the study, methods used, and type of patient cohort and/or time of evaluation after stroke.…”
Section: Introductionmentioning
confidence: 99%